OPTIMALISASI PENINGKATAN SUMBER DAYA MANUSIA PENEGAK HUKUM DALAM IMPLEMENTASI TILANG ELEKTRONIK - Setiawan, Edi; Jauhari, Tontowi (The Juris, 2024)
The use of motorized vehicles in daily life can have a negative impact, namely traffic jams and accidents originating from traffic violations, thus requiring law enforcement efforts. This research aims to find out, analyze and criticize law enforcement regarding traffic violations. This research aims to explore the importance of improving human resources (HR) of the Indonesian National Police (Polri) in implementing electronic traffic fines as an effort to enforce the law against traffic violations. Traffic violations are a common problem in big cities, often caused by the increasing number of motorized vehicles. Electronic fine enforcement, or Electronic Traffic Law Enforcement (ETLE), utilizes technology such as CCTV cameras to detect violations and increase the transparency and efficiency of the legal process. This research uses an empirical juridical type, namely an approach that aims to examine the extent to which law is implemented and functions in society. which in this research is research that uses literature, which involves collecting data through book review literature, journals and official documents. The data collected aims to analyze the relevance of law enforcement theory and practice in the context of electronic fines. The research results show that electronic fines support more modern and efficient law enforcement while helping to improve road safety and order. However, the success of implementing ETLE is very dependent on the competence of Polri’s human resources. Therefore, improving the quality and capacity of Polri’s human resources is very important to ensure the sustainability of digital transformation in traffic law enforcement.